(untitled) (Research, Society and Development, 2020)
Oroantral communication, also known as oroantral fistula, is a problem that often occurs in dentistry, especially during extraction of molars and premolars, in which there is intimate contact with the maxillary sinus, causing the development of an oroantral fistula. Objectives: Analysis of several scientific works already done in order to have greater acquiescence of information and content on the subject. Methodology: A bibliographic analysis of 14 works was carried out, in English and Portuguese, during the period from 2015 to 2020, through the databases: Pubmed, SCIELO, ScienceDirect and LILACS. Results: with this, 85% of the studies showed the effectiveness of using the bichat adipose body in the treatment for oroantral communication; and 15% focused on the use of hard tissue grafts. Final considerations: The use of the Bichat adipose body for the closure of oroantral fistula persists in being a more effective procedure, with regard to improving the patient’s prognosis and less invasive technique developed by the dentist.